The effect of mind maps for those with bodily-kinesthetic intelligence in learning some basic skills in football for juniors (Damu Journal of Sport Sciences, 2024)
The mind maps for those with bodily-kinesthetic intelligence have a role in refining the performance, skills, functional and cognitive of players, as the importance of the research lies in identifying the role of mind maps in learning basic skills and the role of those maps in enhancing the player's physical intelligence, which has an effective role in implementing those basic skills and raising them towards the best in the essence of performance. The researcher believes in the importance of mind maps in the educational process. The researcher worked on studying this problem because of its great impact on learning some basic skills in football. The study also included (20) players out of (60) and exercises were prepared according to Mind maps and their role for those with bodily intelligence and an educational (experimental) method for two months for young football players. It was concluded that exercises prepared with mind maps are important for football players with bodily-kinetic intelligence to develop them physically and skillfully.